The Histopathology of Leg Ulcers - Amun Georg Hofmann; Julia Deinsberger; André Oszwald; Benedikt Weber (MDPI AG, 2024)
Ulcerations of the lower extremities are a frequently encountered problem in clinical practice and are of significant interest in public health due to the high prevalence of underlying pathologies, including chronic venous disease, diabetes and peripheral arterial occlusive disease. However, leg ulcers can also present as signs and symptoms of various rare diseases and even as an adverse reaction to drugs. In such cases, correct diagnosis ultimately relies on histopathological examination. Apart from the macroscopic presentation, patient history and anatomic location, which are sometimes indicative, most ulcers have very distinct histopathological features. These features are found in different layers of the skin or even associated vessels. In this narrative review, we discuss and highlight the histopathological differences of several types of leg ulcers that can contribute to efficient and accurate diagnosis.